Repercussions of the social basis of educational curricula:: Between religious discourse and hate speech - Boudiba, Rabah (Journal of Human Sciences, 2022)
The role of school is not limited to educating young people; rather it goes far beyond that as education derives its concept in any society from the purpose and the goal for which it comes there. In other words, education stems from the prevailing believes or philosophy, be it religious, idealistic or materialistic. And the concept of education is affected by the educational curricula upon which it is built as any educational program builds basically upon the ideological, social and philosophical foundations of a given society. This is fairly evident in the case of Islamic educational curricula that are presented in the form of a religious discourse for students in classrooms. This clearly shows the extent of the impact of religious discourse in educational circles and its social repercussions in the form of hate speech between individuals and peoples.